Kualitas Udara Selama Perjalanan di Kapal Motor Camara Nusantara 3 - Talithania, D.; Salundik; Yani, A. (Jurnal Ilmu Produksi dan Teknologi Hasil Peternakan, 2020)
The Camara Nusantara Ship is a mode of transportation used for transporting cattle to various islands. The journey from Kupang, East Nusa Tenggara to Jakarta took five days. The gases that produced during the trip on the ship were ammonia, methane, carbon dioxide, and carbon monoxide. This aim of research to analysis the air quality of each deck on the ship during transportation and inform the threshold of gas concentration as well as strategies to improve air quality for livestock on the Camara Nusantara Ship. Measurements were taken three times: morning (8 am), noon (12 pm) and afternoon (4 pm). Observation of the gas concentration level was carried out for 10 - 15 minutes. The study was conducted observation, and data analysis was done descriptively. The results showed that the level of gas concentration still in the normal range and below the threshold value and the microclimate on the deck still in the normal range. Another factor that influence air quality were still in the safe category, namely wind speed. Strategies that can be applied to anticipate the decline in air quality by improving the ventilation system on the ship by focusing more on the engine airflow on the vessel.